Penyuluhan Pencegahan Stunting Di Desa Cibugel Kabupaten Sumedang - Renata, Mira; Asmarandani Heryadi Putri; Rifqi; Della Harlia Putri (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This community service activity aims to increase community knowledge and understanding in preventing stunting. The service method is carried out through counseling to provide information regarding stunting prevention. In this counseling, situation analysis is carried out, pre-tests and post-tests are given to assess the knowledge of the counseling participants. The sample from this counseling consisted of 40 mothers who had babies and toddlers. The results of this outreach show an increase in mothers' knowledge regarding stunting prevention before and after receiving outreach information regarding stunting prevention.